Seafaring in the Early Period of the Ancient Middle East: Finds and Written Evidence - Osterman, Jasmina (2011)
In the historical development of society, the Near Eastern region had certainly one of the most prominent roles. Great accomplishments initiated in that area (emergences of writing, social and political forms of communities, cities, states, legal systems, administration…) influenced and determined further course of the history even outside its chronological and geographical boundaries. Likewise, a navigation, as an essential component of the economic life of early communities, played an important role in complex processes of the first highly organized urban societies primarily in the area of Mesopotamia. Traces of the navigation in Mesopotamia are present already from the earliest times. This mostly relates to the sporadic discovery of the remains of fish and shellfish in the settlements, evidence of overseas trade, or to the rare figural representations of boats. With the development of cities, it is clear that in the country with insufficient basic resources (wood, stone, metal) the number of findings that testify to the intensive contacts with distant lands and the dynamic trading relationships increases. Placing products on the closer and more distant markets in order to maintain and improve the social and economic system, require from the people always new demands and challenges that contributed to the further development of the old and creation of the new technologies. These changes culminated in the 4th millennium BC. Kr. with the emergence of the first urban centers with more complex social organization and the elite that ran the physical and human energy potential. All that led to the invention of writing, which gradually became an important tool in the administrative, religious and economic life. In this first texts we have the first written evidence of the river and overseas trade as well as the information about the ships themselves. So we have the records about the delivery of various parts of the ship, lists with the various types of ships, lists with the boats of the gods, votive inscriptions... These written sources, with still present material evidences, largely complete our picture of navigation and shipbuilding in this early period of human history.